Integrasi Nilai-Nilai Ajaran Islam Dalam Pancasila - Darmanto, Darmanto (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) STIT Muhammadiyah Tempurejo, Ngawi, Jawa Timur, 2023)
This writing aims to describe the integration of the values ​​of Islamic religious teaching within the scope of Pancasila. The research approach used is a descriptive case study. This study was conducted by examining and explaining the introduction and understanding of Pancasila values ​​through religious activities. Pancasila as the basis of a nation or the ideology of a nation is in line with the values ​​of Islamic teachings. As a religion that is rahmatan lil `alamin, Islam is very relevant and flexible in all steps of life. Islam governs all believers in all matters, both in personal and social life. The depth of the philosophical values ​​of Pancasila, which is the embodiment of the values ​​of Islamic teachings, should strengthen our position as a religious nation in Indonesia. A civilized religion with respect for all existing religious adherents, as Bun Carno wanted. Therefore, as Indonesian citizens and religious people, we always lead, maintain and apply the values ​​of Pancasila in the life of the nation, state, society and religion.